A mixed methods study investigating factors affecting adherence to Plasmodium vivax malaria primaquine radical cure regimens among migrants along the Myanmar-Thailand border. - April T Ansari; Ko Ko Aung; Htun Htun Win; Candy Beau; Be Nu; Nay Lin Soe; Klay Htoo; Thida San; Tha Gay Wah; Arunrot Keereevijit; Aung Pyae Phyo; Kesinee Chotivanich; et al. (PLOS Global Public Health)
Background The countries within the Greater Mekong Region of Southeast Asia have pledged to eliminate malaria by 2030. Elimination of Plasmodium vivax malaria is challenging as it requires radical cure to prevent relapse. Understanding and facilitating adherence to primaquine radical cure regimens is necessary for malaria elimination. Methods A convergent parallel mixed methods study was conducted to investigate the barriers to and facilitators for completing primaquine treatment of P. vivax infection among mobile migrant communities on the Myanmar-Thailand border. Quantative data were derived from routine malaria consultations. Qualitative data, informed by the social cognitive theory and health belief model, were collected through in-depth interviews with patients and focus group discussions with local health providers and community leaders. Results Of 729 adult patients with primaquine treatment outcomes, 45% did not complete the follow-up of 28 days and were assumed to be non-adherent to primaquine treatment. Patients of Karen ethnicity (OR 1.7, 95% CI 1.2-2.3; p = 0.001) or having a previous episode of malaria from any species (OR 1.6, 95% CI 1.1-2.3; p = 0.007) were more likely to report completing the 14-day primaquine radical cure regimen. Five focus group discussions with front-line healthcare workers and community members and 16 in-depth interviews with patients who were prescribed P. vivax radical cure were conducted. Key themes related to the social cognitive theory included behavioral factors where work outweighed the choice to complete treatment; environmental factors where access to care determined primaquine treatment completion; and cognitive factors having a positive but limited influence on treatment completion. According to the health belief model, prioritizaton of work reduced seeking diagnosis and completing treatment, and often outweighed facilitating factors such as malaria literacy, health education, and social norms; and affected the perceived susceptibility and severity of P. vivax infections. Discussion Work and productivity were identified as primary behavioral factors affecting adherence to primaquine radical cure and follow up in a migrant population. Community support and cultural cues may overcome these barriers. Understanding the rationale of patient adherence to primaquine may help guide programming for P. vivax elimination among migrant populations in resource-constrained settings.